Measuring the economic potential of Tana Luwu: Klassen's Location Qoutient Approach and Typology - Adi Firmanzah; Sri Wahyuny Mustafa; Ahmad Refki Saputra; I Ketut Patra; Jusman (IECON, 2025)
The Tana Luwu area, which includes four districts in South Sulawesi, has a diversity of economic potential that has not been fully mapped optimally. An understanding of the leading sectors is essential to support sustainable regional economic development. Therefore, this study aims to analyze the structure and potential of the economic base sector in the Tana Luwu area using the Location Quotient (LQ) approach and Klassen Typology. The results of the study using the LQ method show the diversity of leading sectors. Luwu and North Luwu Regency place the agriculture, forestry, and fisheries sectors as the main basic sectors among other economic sectors. Palopo City places the Financial Services sector as the main basic sector among other economic sectors. East Luwu Regency places the Mining and Quarrying sector as the main basic sector, and is the only basic sector in economic activities. Klassen's Typology Analysis places several economic sectors in Tana Luwu in the developed and rapidly growing category, while other sectors are still in the developed category but are depressed, developed and left behind. These findings provide the basis for the formulation of more focused economic development policies based on the potential for local excellence.